The Study on How Students of Sunan Drajat Islamic Boarding School Improve Their English Vocabularies - Shobahah, Shohiyah (Research and Community Service Institute (LP2M) of Institute Pesantren Sunan Drajat, 2025)
To respond the technological advances nowadays, Sunan Drajat Islamic boarding school does many efforts to avoid being outdated. One of the ways done is by providing English dormitories to facilitate the students in improving their skill of foreign language. The English athmosphere is also purposely created in order to make the student get used to using English in their daily routine. The conditioned English environment in Sunan Drajat Islamic boarding school requires students to have lots of English vocabularies to help them in speaking English. This current study aims to investigate how English dormitories of Sunan Drajat Islamic boarding school improve the students’ English skill by means of qualitative approach as research methodology. From the research conducted around a month, it was known that the functionaries of English dormitories implement various interesting teaching methods such as singing a song and game to improve students’ bank of vocabularies. Besides, each English dormitory also provides vocabulary board which has the contents of any kinds of English vocabularies on Monday and some English expressions or idioms on Thursday. All English vocabularies and expressions in a week are examined by dorm’s functionaries every Friday morning. The dorm’s functionaries would give any points as punishment for whoever that can not memorize the English vocabularies completely. Finally, the further research in other settings and periods are needed to do in the future to enrich the result of study.